O professor na crise: os saberes da docência diante da dor do outro - Angelo, Fabiane Bortoluzzi (2016)
This study was carried out based on the Training, Knowledge and Professional Development Line of Research linked to the Postgraduate Program in Education of the Federal University of Santa Maria – UFSM. The research group has raised this issue regarding the role of education due to the significant growth of tragic events. The day Kiss Nightclub caught fire, January 27, 2013, was crucial to raise a discussion in this sense. The study aimed at identifying the importance of the aspects referred to the development of knowledge in the teaching path linked to emotional pain resulting from potentially traumatic situations. Therefore, we also aimed at scrutinizing the teaching knowledge that may contribute to the relief of the impacts related to situations such as the one discussed in this study. The research is developed through semi-structured interviews with UFSM professors who have gone through loss of students in that tragedy. In this sense, we propose a tragic hermeneutics of teaching knowledge to assist in developing a training project based on the prevention and protection of society, which is responsibility of several fields of knowledge including Philosophy and Education.